2017
DOI: 10.1596/1813-9450-8119
|View full text |Cite
|
Sign up to set email alerts
|

Deliberative Inequality: A Text-As-Data Study Of Tamil Nadu's Village Assemblies

Abstract: The resurgence of deliberative institutions in the developing world has prompted a renewed interest in the dynamics of citizen engagement. Using text-as-data methods on an original corpus of village assembly transcripts from rural Tamil Nadu, India, this paper opens the "black box" of deliberation to examine the gendered and status-based patterns of influence. Drawing on normative theories of deliberation, this analysis identifies a set of clear empirical standards for "good" deliberation, based on an individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In 2016, Goldblatt et al used satellite imagery in India to examine areas of urbanization in a rapidly developing country [ 15 ]. A World Bank Group additionally reported using natural language processing to study differences between genders when deliberating topics in village meetings transcripts across Tamil Nadu [ 16 ]. Given the expanding use of these methods in international development and survey work, it is only fitting that we take them a step further to assist with monitoring incoming data.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Goldblatt et al used satellite imagery in India to examine areas of urbanization in a rapidly developing country [ 15 ]. A World Bank Group additionally reported using natural language processing to study differences between genders when deliberating topics in village meetings transcripts across Tamil Nadu [ 16 ]. Given the expanding use of these methods in international development and survey work, it is only fitting that we take them a step further to assist with monitoring incoming data.…”
Section: Discussionmentioning
confidence: 99%
“…They have found that women SHG members possess more "oratory competency." This question is further explored in two recent working papers by Parthasarathy et al (2017) and Palaniswamy et al (2017). These authors use text-as-data methods on an original sample of transcripts from Tamil Nadu to evaluate whether and how women participate in village assemblies.…”
Section: Deliberation Under Panchayati Rajmentioning
confidence: 95%
“…Similarly, there is work in Andhra Pradesh by Veeraraghavan (2017) that describes the nature of village government systems using more recent data. There is also recent work on gram sabhas that one of us has been involved with in Tamil Nadu that uses data from 2015 (Parthasarathy, Rao, and Palaniswamy 2017;Palaniswamy, Parthasarathy, and Rao 2017). In the concluding chapter we place our findings based on our older transcripts within the context of this work to offer our thoughts about how much has changed and not changed since the time our data was collected.…”
Section: Advantages and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation